A prospective and retrospective observational study on residual gallbladder stones after cholecystectomy - Indranil Chakraborty; Manojit Sarkar; Arup Kumar Ghosh; Amit Ray (Asian Journal of Medical Sciences, 2024)
Background: A small number of post-cholecystectomy syndrome cases result from residual stones in a lengthy cystic duct or recurrence of lithiasis in a remaining gallbladder (GB) tissue. In laparoscopic procedures, up to 13.3% may involve incomplete GB removal due to surgical complexities and anatomical variations such as adhesions or challenging morphology. Aims and Objectives: (1) To assess the incidence of retained stones in patients undergoing cholecystectomy, (2) to compare incidences among open and laparoscopic cholecystectomies, (3) to study various presenting ways and different investigational methods helping in early diagnosis and proper management, and (4) to study different operative interventions for different cases. Materials and Methods: This was a prospective and retrospective observational study. After getting ethical committee approval and informed consent, 35 patients were included in the study. The study was carried out in the Department of General Surgery at I.P.G.M.E.R./S.S.K.M. Hospital, Kolkata. Results: Most patients were post-open cholecystectomy cases. The incidence of retained GB stones was 4.48%, with females affected 2.8 times more than males. Common symptoms were pain abdomen (80%) and fever (25%). Ultrasonography diagnosed stump calculi in 85.71% of cases; magnetic resonance cholangiopancreatography (MRCP) was preferred when ultrasound was inconclusive. Conclusion: Cases underwent subtotal cholecystectomy or had long cystic duct stumps in rural hospitals, referred to tertiary hospital for further management. Symptoms included pain abdomen, fever, and sometimes jaundice. MRCP confirmed diagnoses before open re-exploration; completion cholecystectomy addressed residual stones for symptom relief and cure.